Classification and Separation of Mineral Materials - Aliyarova Кh.E.; Mamedova, S.B. (Herald of Azerbaijan Engineering Academy, 2025)
One of the most important stages of mineral processing is the separation of mineral materials by granulometric composition. The process is necessary to increase the efficiency of subsequent processing stages, as well as to prepare ore materials for crushing, enrichment and other technological operations. The purpose of size separation is to obtain material of uniform size, increase the efficiency of enrichment processes, and separate the feedstock into fractions for subsequent processing. The main processes of size separation are screening (dry and wet), hydroclassification (classification in an aqueous environment) and aeroclassification (classification in an air environment).